Investigation of the effects of pre-heated linseed oil on performance and exhaust emission at a coated diesel engine - Hazar, Hanbey; Sevinc, Huseyin (Pergamon-Elsevier Science Ltd, 2019)
In this study, the efficiency of using the linseed oil, one of the vegetable oils, in a diesel engine by applying pre-heating was investigated. For this purpose, the pure linseed oil was mixed with diesel fuel at volumetric rates of 30% and 50% and this mixed fuels was used in a four-stroke, single-cylinder, and air-cooled diesel engine. In order to improve the combustion efficiency and reduce the loss of energy of the diesel engine, the parts of the combustion chamber (piston, exhaust, and inlet valves) were coated at a thickness of 300 mu m with Cr3C2, which is a ceramic material having a low thermal conductivity and resisting to high operating temperatures. Plasma spray method was used as the coating method. It was determined that the pre-heating process reduced the viscosity of the linseed oil and also provided a more favorable fuel flow and the coating process had a positive effect on diesel emissions (CO, HC, Smoke, Exhaust Gas Temperature, Brake Thermal Efficiency) of poor quality oils, however pre-heating and coating processes increased the NOx emission. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Linseed oil; Diesel engine; Thermal barrier coating; Exhaust emissions